Communicating openness in deliberation. Issue 2 (3rd April 2017) - Sprain, Leah; Ivancic, Sonia
ABSTRACT: Normative and practical accounts of deliberative democracy cite open-mindedness as a key feature of good deliberation. Yet scholars have often focused on attitude change or self-report measures to empirically demonstrate openness. This paper draws on grounded practical theory to understand openness as a discursive stance in public deliberation. Openness is used to address four practical problems encountered in deliberation: disagreement, opinion formation, dysfunctional community problem-solving, and deliberative sense making. Indicating openness and expressing attitude change are different discursive practices. Expecting participants to refrain from forming opinions before deliberation may be naïve. Instead, participants' eagerness to make sense of deliberation by invoking shared understanding and openness should be used to develop meta-consensus.